Synthesis of α-Mo2C by Carburization of α-MoO3 Nanowires and Its Electrocatalytic Activity towards Tri-iodide Reduction for Dye-Sensitized Solar Cells - Theerthagiri, J.; Senthil, R.A.; Buraidah, M.H.; Madhavan, J.; Arof, Abdul Kariem (Elsevier, 2016)
Nanowire-shaped α-MoO3 was synthesized on a large scale by hydrothermal route. Nanocrystalline α-Mo2C phase was obtained by the carburization of α-MoO3 nanowires with urea as a carbon source precursor. The phase purity and crystalline size of the synthesized materials were ascertained by using powder X-ray diffraction. The shape and morphology of synthesized materials were characterized by field-emission scanning electron microscopy (FE-SEM) and high resolution transmission electron microscopy (HR-TEM). The electrocatalytic activity of α-Mo2C for I−/I3− redox couple was investigated by the cyclic voltammetry. The synthesized α-Mo2C was subsequently applied as counter electrode in dye-sensitized solar cells to replace the expensive platinum.